Improving Spring Melt Calculations of Surface Runoff in the Upper Þjórsá River Using Measured Snow Accumulation - Reynir Óli Þorsteinsson 1982- (2015)
One of the challenges of managing water resources for electricity production in Iceland is the seasonal variation of river discharge. With good discharge predictions it is easier to manage and optimize the hydropower resources. Spring season is of special interest because it brings valuable snowmelt, a resource that is difficult to quantify, predict and simulate. In this project a river catchment in the Upper Þjórsá River was analyzed, in particular the snow accumulation and the resulting spring floods. It involved making hydrological simulations with a HBV rainfall-runoff model. Input meteorological data were obtained from automatic weather stations located in or in the vicinity of the catchment. One of the challenges for these weather stations is to produce reliable precipitation data, especially when the precipitation is in the form of snow. Therefore to adjust the snowpack in the HBV model before spring melt started snow measurements that have been done in the Icelandic highlands were used. The relationship between the snow measurements and the spring melt was analyzed with regression analysis to see if there was a connection between the measured snow water equivalent (SWE) and the resulting spring discharge. The results show that there is a relationship between the measured SWE and spring discharge. The measured SWE provided a valuable point of reference in adjusting the snowpack in the HBV model and thus improving the spring discharge simulations for the catchment. Ein af áskorunum við að stýra nýtingu vatnsauðlindar fyrir raforkuframleiðslu á Íslandi eru árstíðarbundnar sveiflur í árrennsli. Með góðum rennslisspám er auðveldara en ella að hámarka nýtingu vatnsafls. Vorið er sérstaklega áhugavert vegna þess að þá kemur dýrmæt snjóbráð, auðlind sem erfitt er að magntaka, spá fyrir um og herma. Í þessu verkefni er vatnasvið í efri hluta Þjórsár kannað, með áherslu á snjósöfnun og snjóbráð sem fylgir. Í því fólst hermun á vatnasviðinu með regn- og afrennslislíkaninu HBV. Veðurgögn voru fengin frá ...